Livelihood systems of women in Odo-Otin Local Government Area, Osun State, Nigeria (2002)
The situation of women, particularly in the developing countries continues to attract global attention, hence current development trends are people centred, with a view of enhancing their livelihood systems. This study thus examined the livelihood systems of women in Odo-Otin LGA of Osun State, and focused their resource base and predisposition to the livelihood systems. total of 100 women were randomly selected from 4 of the 11 political wards in the LGA. Data were collected through the used structured questionnaire and focus group discussion. Findings revealed that trading is the major livelihood activity among women. However, these women engage in several livelihood activities alongside the major ones. The women obtain input for the livelihood activities from personal savings, loans, husbands, relatives and friends among others.